Մրցունակ արտադրանքը՝ որպես ձեռնարկատիրական ռիսկերի նվազեցման երաշխիք - Հասմիկ Գևորգյան (ՀՀ ԳԱԱ հրատ.)
Из факторов, влияющих на уровень риска предпринимательской деятельности, особо выделяется производство конкурентоспособной продукции. Конкурентоспособность компании и продукции является основным полноценным паказателем, характеризующим эффективность производства, что одновремнно обеспечивает максимальную прибыль предпринимателя и позволяет минимализировать риск. Among the factors influencing on the level of business activity risk, the most risky is the production of competitive products. Competitiveness of companies and production is the basic complete indicator characterizing the effectiveness of production that simultaneously maximizes entrepreneur՛s profit, but also minimizes the risks.
Keywords: Social Sciences; Economic Theory; Commerce